Flexible work arrangement dan work-life balance pada generasi milenial - Dewi, Desak Nyoman Arista Retno; Kinasih Widyanti, Priscila Rosa (Jurnal Psikologi Udayana, 2023)
Currently, millennial generation employees are the working group that dominates employment in Indonesia. Millennial generation employees are characterized by their awareness of getting work-life balance. This is in line with the survey results which show that the majority of millennial employees want a balance between their personal and work lives. The opportunity to apply flexible work arrangements is believed to have an effect on employees' work-life balance conditions. In the COVID-19 pandemic situation, the application of working from home makes implementing flexible work arrangements a challenge to be able to get a work-life balance. This is because the actual working hours exceed the supposed working hours. The purpose of this study is to analyze the effect of implementing flexible work arrangements on work-life balance conditions for millennial employees. This research is a quantitative research with work-life balance as dependent variable and flexible work arrangement as independent variable. The data collection method used a Likert scale with five alternative answer choices. The research subjects are millennial generation employees who work with a hybrid system or a combination of work from home and work from office. Data analysis used non-parametric Kendall's tau-b correlation test because one of the assumption tests was not met. The results showed a significance value of 0.332 > 0.05, which means that there is no influence between flexible work arrangements and work-life balance. There are other factors that are more personal in nature that can support the achievement of work-life balance for millennial generation employees.